Stress and coping strategies of families of pediatric solid organ transplant recipients in times of pandemic - Forner-Puntonet, Mireia; Gisbert-Gustemps, Laura; Castell-Panisello, Eudald; Larrarte, Mauricio; Quintero, Jesús; Ariceta, Gema; Gran, Ferran; Iglesias-Serrano, Ignacio; Garcia-Morán, Annabella; Español-Martín, Gemma; Ibañez-Jimenez, Pol; Ramos-Quiroga, Josep Antoni (Frontiers in Psychology, 2023)
Objective: Pediatric solid organ transplantation (SOT) is a chronic condition that impacts the whole family system. The objective of this study is to evaluate psychopathology, family stress, and coping strategies in families of SOT recipients compared to families of healthy children and adolescents. Moreover, it analyzes if the stress related to the COVID-19 pandemic has had an additional impact on these families. Methods: The sample was recruited between May and July 2021, during the fourth and the fifth wave of the pandemic in Spain. It consisted of 102 families, 51 with a pediatric recipient who had undergone a SOT (liver, kidney, heart, or lung) and 51 healthy controls, matched by child age and gender. A primary caregiver from each family answered an online sociodemographic questionnaire and different tests to evaluate family stress, depression, anxiety, coping strategies and effects of the pandemic on the family. Results: Caregivers were mostly mothers (89.2%). Families of SOT recipients showed greater anxiety (U=863.5, p=0.003) and more total stress, stress related to childcare (t=-2.043; p=0.045) and parent-child interaction stress (U=355.5, p=0.015). SOT families used more avoidance strategies, specifically denial (U=889.5; p=0.010) and abandonment of coping efforts (U=1013; p=0.047), more religious strategies (U=792.5; p=0.031), and fewer social support coping strategies (t=2.098; p=0.038). No differences were found between groups in terms of exposure, impact, and distress more than one year after the start of the pandemic. Conclusions: SOT families showed clinical levels of anxiety, more parent-child interaction stress, and more difficulties in taking care of their child, more avoidance and religious strategies and less use of social support strategies, even four years after transplantation. The pandemic did not have an additional differential effect on SOT families. Caregivers of SOT patients can benefit from psychological interventions focused on parents’ mental health, parent-child connectedness, skill building, and social support aid groups, with attention to multiculturalism and promoting a better balance between caregivers. There is a need for family interventions that are maintained over time. Strategies that offer this support to families through digital resources can facilitate adjustment to chronic illness, especially in pandemic times.